Unimodal and crossmodal working memory representations of visual and kinesthetic movement trajectories - Seemüller, Anna; Fiehler, Katja; Rösler, Frank (Acta psychologica, 2011)
The present study investigated whether visual and kinesthetic stimuli are stored as multisensory or modality-specific representations in unimodal and crossmodal working memory tasks. To this end, angle-shaped movement trajectories were presented to 16 subjects in delayed matching-to-sample tasks either visually or kinesthetically during encoding and recognition. During the retention interval, a secondary visual or kinesthetic interference task was inserted either immediately or with a delay after encoding. The modality of the interference task interacted significantly with the encoding modality. After visual encoding, memory was more impaired by a visual than by a kinesthetic secondary task, while after kinesthetic encoding the pattern was reversed. The time when the secondary task had to be performed interacted with the encoding modality as well. For visual encoding, memory was more impaired, when the secondary task had to be performed at the beginning of the retention interval. In contrast, memory after kinesthetic encoding was more affected, when the secondary task was introduced later in the retention interval. The findings suggest that working memory traces are maintained in a modality-specific format characterized by distinct consolidation processes that take longer after kinesthetic than after visual encoding.